Multi-year water balance dynamics of a newly constructed wetland, Fort McMurray, AB - Nicholls, Erin (2015)
Oil sands mining in Alberta completely transforms the natural boreal landscape of upland forests, wetlands and lakes into open pits, tailings and overburden piles. By law, industry is required to return the landscape to its pre-disturbance land capability. While previous reclamation efforts have mainly focused on upland forest ecosystems, rebuilding wetland systems on soft tailings has only recently become a research focus. The dry, sub-humid climate and high salinity levels of underlying mining material complicate reconstruction of wetlands within this region. In 2012, Syncrude Canada Ltd. completed construction of the Sandhill Fen Watershed (SFW), a 52-ha upland-wetland system to evaluate wetland reclamation strategies. SFW includes an active pumping system, upland hummocks, a fen wetland and underdrains. This study examined the watershed-scale water balance in the first two years after commissioning (2013 and 2014). The first paper presents a semi-distributed water balance approach examining the fluxes and stores of different landscape units. Artificial pumping controlled the water balance in 2013, with approximately double the annual precipitation pumped in and out from May-Oct 2013, causing large water table fluctuations. In 2014, pump management was more passive, and water balance controlled by vertical fluxes. In the second paper, growing season ET rates and controls were assessed using data from three eddy covariance towers in the uplands and lowlands. Average ET rates between uplands and lowlands were similar, with average rates of 2.41 – 2.52 mm d-1. ET was radiatively controlled at all sites. Energy partitioning and ET rates are similar to natural boreal peatlands within the area, however upland areas are expected to increase in ET rates as LAI increases and vegetation matures. This study provides critical quantitative data on the early years of a highly managed watershed. Long-term monitoring is necessary, as water balance dynamics will evolve with vegetation development and climate cycles. Thesis Master of Science (MSc)